A systematic review on renal and bladder dysfunction after endoscopic treatment of infravesical obstruction in boys. - Pauline M L Hennus; Geert J M G van der Heijden; J L H Ruud Bosch; Tom P V M de Jong; Laetitia M O de Kort (PLoS ONE)
Background Posterior urethral valves (PUV) may cause subtle to severe obstruction of the urethra, resulting in a broad clinical spectrum. PUV are the most common cause of chronic renal disease in boys. Our purpose was to report the incidences of kidney and bladder dysfunction in boys treated with endoscopic valve resection for PUV. Methodology We searched MEDLINE and EMBASE databases until 1st of July 2011, to identify original papers that described outcome of endoscopic valve resection (EVR) in boys. We extracted information on (1) patient characteristics and clinical presentation of PUV related to outcomes and (2) the post-treatment absolute risks for kidney and bladder dysfunction. Principal findings Thirty-four studies describing renal function, vesicoureteral reflux (VUR), incontinence, and urodynamic bladder function after EVR in 1474 patients were retrieved. Patients treated for PUV show high percentages of chronic kidney disease (CKD) or end stage renal disease (ESRD), 22% (0-32%) and 11% (0-20%), respectively. Elevated nadir serum creatinine was the only independent factor associated with renal failure. Before treatment, VUR was present in 43% of boys and after EVR, VUR was present in 22%. Post treatment, 19% (0-70%) was reported to suffer from urinary incontinence. Urodynamic bladder dysfunction was seen in many patients (55%, 0-72%) after treatment of PUV. Conclusions The reported cumulative incidence of renal and bladder dysfunction in patients with PUV after endoscopic PUV treatment varies widely. This may reflect a broad clinical spectrum, which relates to the lack of a standardised quantification of obstruction and its severity. Moreover, the risk of bias is rather high, and therefore we put little confidence in the reported estimates of effect. We found elevated nadir serum creatinine as a predictor for renal dysfunction. In order to be able to predict outcomes for patients with PUV, an objective classification of severity of obstruction is mandatory.